(untitled) (Research, Society and Development, 2022)
Modifications of implants by means of surface treatments are performed to optimize the biochemical interactions of the bone deposition process. However, if on the one hand they favor the adhesion of blood elements, on the other hand they can also enable the formation of biofilm. This study evaluated the adherence of blood cells and Escherichia coli in titanium discs submitted to surface treatments by anodic oxidation (OA), sandblasting followed by acid etching (JAT) compared with untreated discs (Li). To evaluate the adherence of microorganisms were performed: atomic force microscopy; Field Emission Gun Scanning Electron Microscopy (FEG-SEM); biofilm formation was evaluated by spectrophotometer turbidity analysis and colony forming unit (CFU/mL) before and after simulated brushing. For blood cell adherence, the blood collected from a patient was deposited and fixed on the discs and analyzed in the FEG-SEM being classified according to the "Blood Element Adherence Index". The results showed a slight increase in the adhesion of microorganisms in samples treated by anodic oxidation. However, the microorganisms were distributed singly and not in conglomerates, with no biofilm formation unlike the Li group. Regarding the adherence of blood elements, the Li group showed higher adherence and lower amount was found in the JAT group, but there was no statistically significant difference between the groups. The results of this study suggest that anodic oxidation treatment may favor the adherence of blood cells and fibrin mesh, contributing to the early stages of bone deposition.